Binary frequency-shift keying (BFSK) transceiver design for galvanic intra-body communications / I.W. Ibrahim … [et al.] - Ibrahim, I.W.; Razak, A.H.A.; Khir, R.N.; Ahmad, A. (Universiti Teknologi MARA, 2019)
The development of health monitoring technologies has been increasing due to the increasing demand in the healthcare system. In order to continuously monitor critical patient health vital sign such as heart rate and glucose level, communication between the miniature sensor on the human body already successfully deployed using radio frequency (RF) technology, however it's consumed high power. Intra-body communication (IBC) technology is an excellent alternative as it provides flexibility, portability and consumed less power. IBC system used the human body to transfer the transmission data. In this paper, new IBC transceiver based on Binary Frequency Shift Keying (BFSK) was designed. IBC transmitter modulated binary input data to specific frequency before transmitting through the human body. Then IBC receiver demodulated the receiving signal into binary to be processed. The design was implemented using the FPGA board. The galvanic Coupling IBC method was chosen, and the result shows that the receiving data at the receiver is precisely the same as transmitting data.